TALKING TO YOUNG PEOPLE ABOUT SEX IN SOUTH AFRICA: NEIGHBORHOOD AND SOCIAL INFLUENCES. Issue 6 (August 2014) - Tarantino, Nicholas; Anthony, Elizabeth R.; Zimmerman, Lindsey; Armistead, Lisa P.; Cook, Sarah L.; Skinner, Donald; Toefy, Yoesrie
<x xml:space="preserve">Abstract</x> Our study seeks to untangle systemic influences on specific family dynamics understudied in a non‐Western context. Specifically, we examine the associations between caregivers' perceptions of neighborhood cohesion, neighborhood safety, and social support, and one aspect of parenting relevant to the South African community from which data were drawn, caregiver–youth communication about sex. Multivariate regression models demonstrate interactive relationships among our variables of interest (p ≤ .05). For caregiver–youth dyads (N = 99), living in a neighborhood caregivers perceived to be relatively cohesive or safe was associated with differential relationships (i.e., conditional effects; p ≤ .07) between caregiver social support and youth report of communication about sex. Our findings indicate that neighborhood and social‐level influences on parenting are not universal. Moreover, cross‐cultural adaptations of family‐based behavioral interventions to prevent HIV should consider the role of caregiver social support within diverse neighborhood contexts.